2013
DOI: 10.1002/jts.21864
|View full text |Cite
|
Sign up to set email alerts
|

The Bidirectional Dyadic Association Between Tendency to Forgive, Self‐Esteem, Social Support, and PTSD Symptoms Among Terror‐Attack Survivors and Their Spouses

Abstract: This study examined the dyadic association of terror attack survivors’ and spouses’ internal resources, tendency to forgive (self, others,and situational forgiveness), self-esteem, and the external resource of social support, as associated with victims’ and spouses’ posttraumatic stress disorder (PTSD) symptoms, using the actor–partner interdependence model. Based on lists by the One Family organization in Israel, 108 couples participated in the study. The study results demonstrate that in the dyad relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 56 publications
4
22
0
Order By: Relevance
“…However, results of the studies that include only one trait are inconsistent (Brown & Phillips, 2005;Turnage et al, 2012;Weinberg, 2013;Macaskill, 2012;Sastre et al, 2003) . Our findings might indicate that positive psychological characteristics are important for positive forgivingness but they are meaningless for reducing the negative tendency to forgive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, results of the studies that include only one trait are inconsistent (Brown & Phillips, 2005;Turnage et al, 2012;Weinberg, 2013;Macaskill, 2012;Sastre et al, 2003) . Our findings might indicate that positive psychological characteristics are important for positive forgivingness but they are meaningless for reducing the negative tendency to forgive.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have verified this implication. They found associations between self-esteem and both types of forgiveness -episodic (Eaton, Struthers, & Santelli, 2006) and dispositional (Eaton, Struthers, & Santelli, 2006;Turnage et al, 2012;Weinberg, 2013;Shuguang et al, 2016). Their results have indicated that the higher a person's self-esteem, the less likely they were to avoid or seek revenge against a transgressor (Eaton, Struthers, & Santelli, 2006).…”
Section: Positive Orientation and Forgivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived social support, rather than the actual support received, plays an important role in predicting psychological well‐being and HRQOL (Cook et al. , Weinberg ). In contrast, impaired social support is one of the most powerful risk factors for PTSD vulnerability (Brewin et al , Ozer et al ), as well as depression (Cruwys et al , Lindfors et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, any resilience building initiative requires an initial identification of patients with impoverished mastery, so treatment access and adherence may be facilitated. Perceived social support, rather than the actual support received, plays an important role in predicting psychological well-being and HRQOL (Cook et al 2009, Weinberg 2013. In contrast, impaired social support is one of the most powerful risk factors for PTSD vulnerability (Brewin et al 2000, Ozer et al 2003, as well as depression (Cruwys et al 2013, Lindfors et al 2014.…”
Section: Discussionmentioning
confidence: 99%